Factors enabling Micro, Small and Medium enterprises within the manufacturing sector to adopt circular economy Interventions - Myres, Hugh (University of Pretoria, 2023)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2022.